Analisis Konsep Perkembangan Ilmu Komunikasi Islam di Indonesia - Efendi, Erwan; Zahra, Anggraini; Alfitrah, Aldi; Pratama, Sarfiyan; Kumala, Siti; Habibi, Nahwa (VISA: Journal of Vision and Ideas, 2023)
As a science, Islamic Communication has main sources that have great potential to be explored to build and develop Islamic Communication Science. These sources are the Al-qur’an and Sunnah. Even though it is not collected in one place, the raw materials for Islamic Communication Science which are found in many places in the Al-qur’an and Sunnah make it possible to format Islamic Communication Science systematically, so that it becomes a science that is easily utilized by academics and society in general. The method used in this research use the Systematic Literature Review (SLR) to find out the most appropriate method for designing enterprise architecture in government agencies. This research implements three stages, namely: planning, implementation, and analysis of the results, which involve analyzing the results of the Literature Review that the author has carried out. This research shows that the Al-qur’an and hadith as well as the books of previous scholars contain a lot of information about communication. However, books about Islamic Communication and other supporting contemporary books in the context of building science such as Communication Science in general only started to develop in the 20th century. On the other hand, this development is also influenced by the development of Communication Science, especially when communication technology and communication media develop rapidly in line with the needs of human nature as social creatures.